Financing party branches: Evidence from the German federal system. Issue 2 (15th March 2023) - Jacob, Marc S.
ABSTRACT: Adequately financed branches contribute to the integration of regional interests into statewide parties. Yet, we have limited knowledge about the determinants of branches' varying income levels in federal contexts. To address this shortage, this article elucidates why branches receive donations from citizens and businesses to different degrees. I hypothesise that party competition at the state level, the difference in regional economic performance and parties' historical legacies can account for the level of branches' donation revenue. Analysing German statewide party branches' income from 2009 to 2017, this study finds support for the facilitating impact of state and federal electoral contests on donation levels. Regional economic disparities, by contrast, only marginally affect donation revenues. At the same time, parties' path-dependent developments help explain asymmetries in average revenue levels between western and eastern branches. The study's findings suggest that intense regional party competition contributes to branches' financial independence within the statewide party organisation.